Традиційні сюжети і образи в загальнокультурному універсумі (А.Є.Нямцу «Міф. Легенда. Література») - Торкут, Н. (Інститут літератури ім. Т.Г.Шевченка НАН України, 2009)
В статье представлена рецензия на книгу «Миф. Легенда. Литература» (2007), которая обобщает ценный опыт многолетних исследований украинской школы компаративистики, возглавляемой Анатолием Евгеньевичем Нямцу. В монографии разработана комплексная модель историко-литературного анализа традиционных сюжетов и образов. The author of the article gives a review of the book “Myth. Legend. Literature” written by A.Niamtsu (2007). The monograph generalizes the precious experience of research that has been conducted for many years by the Ukrainian school of comparative studies under the leadership of Anatoly Niamtsu. The book offers a compex algorithm for analysing traditional plots and images of World literature.